Rekonstruksi Nilai-nilai Akhlakul Karimah pada Santri Putra di Pondok Pesantren Motivator Qur’an Darussalam Probolinggo - Karim, Abd.; Wisudaningsih, Endah Tri; Susanti, Salamah Eka (ISLAMIKA, 2024)
This research aims to reconstruct the values of Akhlaqul Karimah among male students at Pesantren Motivator Qur'an Darussalam. The research background reflects the challenges faced by pesantren in achieving character formation goals in line with pesantren values, including rule violations by some students. The research methodology uses a qualitative approach with a case study research type. Data collection techniques include observation, documentation, and interviews. The data analysis technique used in this research is the interactive analysis model by Miles and Michael Huberman, consisting of Data Reduction, Data Display, and Drawing Conclusions (Verification). Data validity is ensured through credibility, transferability, dependability, and confirmability. The research findings indicate that in the effort to reconstruct akhlaq values, pesantren employs four main approaches: personal development, monitoring student interactions, providing exemplary role models, and motivation as strategies to ensure behavioral alignment with religious values and pesantren norms.